2006
DOI: 10.1017/s0022112006009402
|View full text |Cite
|
Sign up to set email alerts
|

The stress system in a suspension of heavy particles: antisymmetric contribution

Abstract: The nature of the stress in a suspension of equal homogeneous spheres all subject to the same force, such as weight, is considered; inertial effects are neglected. This study builds upon some of the well-known work devoted to this problem by the founder of the Journal of Fluid Mechanics, Professor George K. Batchelor. After developing a general theory, the antisymmetric part of the stress tensor is considered in detail. It is shown that, in addition to a term already found by Batchelor and characterized by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…To validate the model, we apply it to the case of viscous droplets and Navier-slip spheres. The results correct and extend several prior results for constitutive equations of rigid spheres (Einstein 1906(Einstein , 1911Prosperetti 2004;Prosperetti et al 2006;Jin et al 2018;Zhou & Prosperetti 2020) and viscous droplets (Taylor 1932;Raja, Subramanian & Koch 2010), and are shown to be consistent with experimental observations. The study is concluded with a discussion of results and future prospects.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…To validate the model, we apply it to the case of viscous droplets and Navier-slip spheres. The results correct and extend several prior results for constitutive equations of rigid spheres (Einstein 1906(Einstein , 1911Prosperetti 2004;Prosperetti et al 2006;Jin et al 2018;Zhou & Prosperetti 2020) and viscous droplets (Taylor 1932;Raja, Subramanian & Koch 2010), and are shown to be consistent with experimental observations. The study is concluded with a discussion of results and future prospects.…”
Section: Introductionsupporting
confidence: 89%
“…These limitations can be overcome by the phase-averaging method of Zhang & Prosperetti (1994a, 1997, which, in principle, can be used to compute the ensemble average of any field in a suspension of arbitrary composition. However, their methods require the use of high-rank tensors, and hence have largely been limited to dilute suspensions of inviscid spherical droplets (Zhang & Prosperetti 1994b) or rigid, solid spheres (Zhang & Prosperetti 1997;Prosperetti 2004;Prosperetti, Zhang & Ichiki 2006) due to the mathematical complexity involved in separating field averages in the fluid from those in the particles, which are most tractable as moments of the hydrodynamic surface traction.…”
Section: Introductionmentioning
confidence: 99%
“…Both terms vanish in Stokes flow as shown in Ref. 5. The third term gives rise to the vector V defined in Eq.…”
Section: ͑C4͒mentioning
confidence: 75%
“…This is the procedure followed in our earlier paper. 5 Bardet and Verdoulakis 51 have calculated the stress in a granular medium by applying the principle of virtual work and found it to have an antisymmetric component when the forces on the particles have nonzero moment about their centers. This is similar to our result ͑20͒ and, in fact, their Eq.…”
Section: ͑68͒mentioning
confidence: 99%
See 1 more Smart Citation